Gone - Grant, Michael, 1954- (New York : HarperTeen, 2009)
In a small town on the coast of California, everyone over the age of fourteen suddenly disappears, setting up a battle between the remaining town residents and the students from a local private school, as well as those who have "The Power" and are able to perform supernatural feats and those who do not.
Copyright date: 2008.
013-017.
620
Accelerated Reader
Keywords: Teenagers -- Juvenile fiction; Good and evil -- Juvenile fiction; Teenagers -- Fiction; Good and evil -- Fiction; Teenagers -- Fiction; Good and evil -- Fiction